Pengurangan Perilaku Bullying pada Sekolah Ramah Anak - Riza Wardefi; Muhammad Hidayat; Rahmi Wiza (ISLAMIKA, 2023)
The background of this exploration is that schools are no longer a safe place from bullying and violence because the perpetrators are teachers, principals or friends. It is important to see examples of schools that are capable of being role models as Sekolah Ramah Anak (SRA), in this case MTsN 6 Padang. This research problem is to analyze the model of Child Friendly School (SRA) at MTsN 6 Padang, and the implementation of policies Child Friendly School (SRA) in reducing bullying at MTsN 6 Padang. The analysis theory of this study uses social fact analysis in Foucault's perspective. Foucault sees bullying as a target of power in the form of power and control relations in the field of education in schools. This exploration method system uses a qualitative with a descriptive type and case study approch. The results of the study show that the SRA model at MTsN 6 Padang is a Child Friendly Teaching Model (CFTM) based on 3P: Provision, Protection, and Participation. The implementation of the SRA policy in reducing bullying at MTsN 6 Padang is; 1) dissemination of anti-bullying, 2) preparation of a child's rights-based curriculum, 3) improvement of education of teachers and education staff, 4) completeness of child-friendly school facilities and infrastructure, 5) involving representatives of students as the implementing team, 6) increasing the participation of parents under supervision of child development.